Tahliil Istikhdaami al-Mufradaat al-'Arabiyyat al-Muqtaridhah Fii al-Lughat al-Induuniisiyyat - Hermiwati, Hermiwati; Hadziq, Muhammad Fadhil; Pelealu, Nanda Dzikrillah; Mustofa, Syaiful (Jurusan Pendidikan Bahasa Arab IAIN Ponorogo, 2024)
The objectives of this study were to determine the meaning of the word